Severe Anemia and Six-Month All-Cause Mortality in Chronic Kidney Disease Patients Undergoing Hemodialysis - Langgeng Perdhana; Shofa Chasani (Universitas Nahdlatul Ulama Surabaya, 2022)
Anemia is often found in patients with Chronic Kidney Diseases (CKD). Anemia can affect poor outcomes in hemodialysis patients. However, no publications examined the role of severe anemia as a predictor factor in six-month all-cause mortality in hemodialysis patients. Therefore, further study was needed to answer these questions. This study aimed to determine the role of severe anemia and six-month all-cause mortality in hemodialysis patients. The cohort design study was carried out from October 2019 to March 2020 at the Hemodialysis Unit of Roemani Muhammadiyah Hospital Semarang. The dependent variable was severe anemia, defined as hemoglobin levels <8.0 g/dL. The mortality rate was investigated over six months after the baseline measurements. Among 85 respondents, 35 (41.2%) respondents were categorized into severe anemia, and 50 (58.8%) respondents were categorized into non-severe anemia groups. The respondents consisted of 54 (63.5%) males and 31 (36.5%) females. The hemoglobin level in the severe and non-severe anemia groups was 7.2 ± 0.6 and 9.5 ± 1.2 (mean ± standard deviation). The Kaplan Meier survival curve showed that the non-severe anemia group had a higher survival rate than the severe anemia group (98.0% vs. 82.9%, p = 0.011). The Cox regression analysis found a significant relationship between anemia severity and 6-month all-cause mortality in hemodialysis patients (p = 0.027; Hazard ratio: 9.3). Severe anemia plays a role as a predictor factor in six-month all-cause mortality among hemodialysis patients.